The women's movement and women's employment in nineteenth century Britain - Jordan, Ellen, 1938- (Routledge, 1999)
Ellen Jordan's treatment of the expansion of middle-class women's work is perhaps the most comprehensive available and is a valuable complement to existing works on the social and economic history of women.
Keywords: Women -- Employment -- Great Britain -- History -- 19th century.; Feminism -- Great Britain -- History -- 19th century.; Women -- Great Britain -- Social conditions.; Femmes -- Travail -- Grande-Bretagne -- Histoire -- 19e siècle.; Féminisme -- Grande-Bretagne -- Histoire -- 19e siècle.; Femmes -- Grande-Bretagne -- Conditions sociales.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Feminism; Women -- Employment; Women -- Social conditions; Great Britain; Berufstätigkeit; Frau; Frauenbewegung; Großbritannien; Vrouwenarbeid.; Vrouwenbeweging.; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Geschichte 1840-1900.; 1800-1899; History